Studi Deskriptif Mengenai Strength-Based Parenting pada Mahasiswa - Marissa Chitra Sulastra; Vida Handayani (Humanitas (Jurnal Psikologi), 2021)
This research aims to get a description of strength-based parenting (SBP) on college students. The topic of parenting has been widely researched by experts. One of the parenting theories that is currently being developed from a positive psychological approach is strength-based parenting (SBP). The research about SBP, especially in Indonesia, is still limited. This research was conducted on 94 students of the Faculty of Psychology at "X" University by filling out a questionnaire. The questionnaire consisted of 14 items designed by Lea Waters (2017) using a Likert scale. All items are valid with validity values from 0.316 to 0.636. The reliability value of the questionnaire was 0.914 so it is reliable. Data analysis techniques using frequency distribution. This study obtained that 71% of college students appreciate the SBP conducted by their parents is in the high-use category. So, it can be said that most parents already know college students’ strengths and encourage them to use these strengths in their daily lives. The benefits of this research can be used as a basis for other researchers to research on SBP. Also, parents are expected to be able to use this research as a basis to help themselves to do parenting based on SBP. Keywords: Parenting, Positive Psychology, Strength-based Parenting